Bagaimana Daya Saing Ekspor Minyak Sawit Mentah Negara ASEAN di Pasar India dari 2011 hingga 2022? - Bancin, Hardi Dominikus; Sigit Sugiardi; Asti (Universitas Medan Area, 2025)
India is the world's largest importer of Crude Palm Oil (CPO), holding a market share of 20% in 2022, making it a highly significant market for CPO-producing countries, including ASEAN nations. CPO serves as a primary export commodity for Indonesia, Malaysia, and Thailand. This study aims to analyze the export competitiveness of CPO from ASEAN countries to India using the Relative Comparative Advantage (RCA) method. Export volume data from 2011 to 2022 were analyzed to comprehend the trade dynamics and competitive positions of ASEAN countries in the Indian market. The research findings indicate that Indonesia boasts the highest comparative advantage with an average RCA value of 18.25, followed by Malaysia (15.76), Cambodia (14.79), Thailand (2.15), and the Philippines (2.46). Overall, ASEAN countries demonstrate a comparative advantage in the Indian market with an average RCA value of 8.60. These findings offer crucial insights for policymakers and industry stakeholders to enhance the export competitiveness of CPO in the international market. This study contributes significantly to understanding the CPO trade dynamics between ASEAN countries and India, providing a foundation for more effective policy formulation to improve market positioning and export competitiveness of CPO in the global market.